Fabrication and Characterization of Chromium Nanotube Using (AAO) Template (Journal of University of Babylon for Engineering Sciences, 2017)
In the current research, the fabricating of Cr nanotubes was done by electrochemical deposition in anodic aluminum oxide (AAO) as template. Characterization of fabricated Cr nanotubes were a achieved by XRD, SEM/EDS and TEM. These techniques indicated that the deposited chromium nanotubes have high purity within experimental conditions, the peaks in XRD was good agreement with JCPDS cards, SEM images showed the growth of ordered nanotubes in one plane perpendicular to the template (AAO). The purity of fabricating nanotubes was confirmed by EDS analysis, while the produced single walled nanotubes was shown from TEM images with open ends of tubes. 60 nm as diameter was obtained for fabricating Cr nanotubes.The fabrication of Cr nanotubes suggests producing quintuple bonds (Cr ≡ Cr) to form tubes without any chance to deposit chromium as particles.